Archives, recherches et cultures lesbiennes. - Archives, recherches et cultures lesbiennes (ARCL) (Paris : ARCL, 1987)
Fonds Suzan Daniel (FSD)
Redactie : B.P. 662, 75531 Paris Cedex 11
Frans
Periodiek